Analysis of Inflammation Biomarkers in Exhaled Breath Condensate in Patients with COPD Combined with Peripheral Arterial Disease - S. N. Kotlyarov; I. A. Suchkov; O. M. Uryasev; A. A. Kotlyarova (SINAPS LLC, 2023)
Background. Chronic obstructive pulmonary disease (COPD) is one of the most signiﬁcant diseases due to its high prevalence and impact on prog- nosis. The frequency of exacerbations and comorbidity are important factors inﬂuencing the course of COPD. It is believed that local and systemic inﬂammation may underlie this heterogeneous course of COPD. In this regard, assessment of local inﬂammation activity in the respiratory tract may be useful to assess the course of COPD. Aim. To study molecular mechanisms of COPD and assess inﬂammation biomarkers in the exhaled breath condensate (EBC) in patients with COPD with the phenotype of frequent exacerbations combined with peripheral atherosclerosis. Materials and Methods. Bioinformatic analysis of data from Gene Expression Omnibus (GEO) was performed to examine gene ontology of differentially expressed genes in COPD. Proinﬂammatory cytokines interleukin-1 beta (IL-1β) and tumor necrosis factor alpha (TNFα) in EBC in COPD patients without concomitant atherosclerotic cardiovascular disease (ASCVD) in the stable course phase, in patients with COPD with the phenotype of frequent ex- acerbations and peripheral artery disease (PAD) compared with healthy controls were examined. Results. Differentially expressed genes are involved in biological processes and signaling pathways according to the Kyoto Encyclopedia of Genes and Genomes (KEGG pathway) associated with the immune response that may link the development and progression of COPD and atherosclerosis. Patients with COPD combined with atherosclerosis had higher values of IL-1β and TNFα in EBC compared with controls (p <0.001). COPD patients with frequent exacerbations and PAD had the highest levels of IL-1β and TNFα in EBC compared with patients without ASCVD (p=0.0038 and p=0.0005, respectively). Conclusion. TNFα and IL1-β levels in EBC are elevated in COPD patients with frequent exacerbations and PAD, which may indicate the presence of local inﬂammation in the airways, the severity of which is associated with the clinical course of COPD.